Eksplorasi Faktor Keberlanjutan Sosial dalam Konstruksi Berkelanjutan - Rostiyanti, Susy; Fassa, Ferdinand; Sutanto, Leovandi (Jurnal Bangunan, Konstruksi & Desain, 2025)
Environmental, economic, and social factors are three critical dimensions that influence sustainable construction. Nevertheless, stakeholders in the construction sector remain insufficiently cognizant of the social dimension of sustainability. This study aims to elucidate the elements associated with the social dimension of sustainability and to identify factors deemed significant by stakeholders in the construction industry. This study employed a quantitative research methodology. A questionnaire was developed based on a review of pertinent literature and formed using a Likert scale. The questionnaire was subsequently sent to stakeholders in the construction industry, and the findings were evaluated utilizing the Relative Importance Index (RII). The findings indicate that three critical variables in social sustainability pertain to internal project stakeholders: workplace safety and health, stakeholder interaction, and worker training and education. These three elements are the essential components of social sustainability. Factors related to external stakeholders, such as the community around the project site, remain a secondary concern for construction industry players today.